Students’ Challenges and Strategies in Learning English for the Fourth Semester of English Education Study Program STKIP PGRI Lubuklinggau - Siti Fatimah Aprillita; Ayu Oktaviani; Dewi Syafitri (Linguistic, English Education and Art (LEEA) Journal, 2022)
This research aimed to identify students’ challenges and strategies in learning English for the fourth semester of English education study program at STKIP PGRI Lubuklinggau. The method used qualitative survey in this research. The population and sample or research subject were 32 students taken by simple random sampling total sample were 16 students. Data collection by using questionnaire and interview. Technique for analyzing the data used findings the result of percentage. The result of this research were trigger students ability, Second, made students think about English, Third, made students improving students’ skills, Fourth, made learning easier andFive, as students’ motivation in learning English. In conclusion, the challenges is very important for students in learning English because it can help students easier in learning English. Keywords: Challenges, Learning English, Strategies